2017
DOI: 10.1192/bjp.bp.116.181107
|View full text |Cite
|
Sign up to set email alerts
|

Mood disorders in first- and second-generation immigrants: Systematic review and meta-analysis

Abstract: Although there are consistent reports of higher psychosis rates among immigrants, the information on mood disorders is limited.To review and quantify the difference in incidence of mood disorders in first- and second-generation immigrant (FGI and SGI) groups non-immigrants.PubMed, EMBASE and PsycINFO were searched for articles from cohort studies reporting incidence of mood disorders among FGIs and SGIs.Eighteen studies met our inclusion criteria. The summary relative risk (RR) for FGIs was 1.25 (95% CI 1.11-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 54 publications
(139 reference statements)
1
53
4
2
Order By: Relevance
“…Danish population data also showed lower incidence rates of affective and personality disorders among immigrants than native Danes . In contrast, two meta‐analyses of population‐based studies suggest an overall modest increase in risk of mood disorders in immigrants, although considerable heterogeneity existed across studies . The seemingly conflicting findings across studies may be explained by the heterogeneous nature of immigrant populations.…”
Section: Introductionmentioning
confidence: 95%
“…Danish population data also showed lower incidence rates of affective and personality disorders among immigrants than native Danes . In contrast, two meta‐analyses of population‐based studies suggest an overall modest increase in risk of mood disorders in immigrants, although considerable heterogeneity existed across studies . The seemingly conflicting findings across studies may be explained by the heterogeneous nature of immigrant populations.…”
Section: Introductionmentioning
confidence: 95%
“…Previous meta-analyses have tended to aggregate data from a diversity of settings and ethnic groups [8,9,[19][20][21][22][23] combining ethnic minority people regardless of diverse identities and pre-and post-migrant experiences [19,22,23]-against a 'native' reference population. Although some reviewers have synthesised and reported summary estimates for studies conducted in the UK [9] or England more specifically [11,15], data for some ethnic groups has not been pooled largely due to the limited evidence base (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the incidence of diagnosis of affective psychoses is not as well understood. Some reports indicate excess diagnosis risks in both types of psychoses for ethnic minority or migrant groups [24][25][26][27], while other reports have demonstrated that the diagnosis of non-affective psychoses, or schizophrenia specifically, is particularly raised [11,23], or that the diagnosis of affective psychoses may not be significantly higher for certain ethnic minority compared to the reference populations [20,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indeed indicated that immigrants, especially refugees, have a greater risk of developing some mental illnesses than native populations [1,[3][4][5][6]. In many countries, psychotic disorders, mood disorders, and post-traumatic stress disorders have been more common among immigrants than native populations [3][4][5]7].…”
Section: Introductionmentioning
confidence: 99%